MUSEUM KOMIK DI BANJARBARU - Subhan, Muhammad Rifky Faisal; Saud, Mohammad Ibnu (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Indonesian comics have a long and growing history in very diverse categories and had played an important role in the past as a medium for visual communication in Indonesia. The problems faced are reintroducing the diversity of the history of comics in Indonesia from the beginning to the present through the design of the museum in chronological storytelling spaces. The method for solving the problem is by using the symbolic analogy method, by analogizing the main part of the comic, namely the story panels as spaces, the trenches between panels as circulation between spaces, and the relationship between panels as story sequences. The concept of sequences between panels with breaks in the form of trenches is an option in producing designs, namely connecting spaces and spaces that are different from each other with a linear and chronological circulation.